Src is the connecting player between PKA activation and hyperpolarization through SLO3 regulation in mouse sperm - Stival, Cintia Estefanía (2015)
Plasma membrane hyperpolarization is crucial for mammalian sperm to acquire acrosomal responsiveness during capacitation. Among signalling events leading to mammalian sperm capacitation, the immediate activation of protein kinase A plays a pivotal role, promoting the subsequent stimulation of protein tyrosine phosphorylation that associates with fertilizing capacity. We have previously shown that mice deficient on the tyr-kinase cSrc are infertile, and exhibit an improper cauda epididymis development. It is therefore not clear whether lack of sperm functionality is due to problems in epididymal maturation or to the absence of cSrc in sperm. To further address this problem, we investigated the kinetics of cSrc activation using anti phosphor Y416-cSrc antibodies that only recognize active cSrc. Our results provide evidence that cSrc is activated downstream of PKA and that inhibition of its activity blocks the capacitation-induced hyperpolarization of the sperm plasma membrane without blocking the increase in tyrosine phosphorylation that accompany capacitation. In addition, we show that cSrc inhibition also blocked the agonist-induced acrosome reaction and that this inhibition is overcome by pharmacological hyperpolarization. Considering that the capacitation-induced hyperpolarization is mediated by SLO3, we evaluated the action of cSrc inhibitors on heterologously expressed SLO3 channel. Our results indicate that, similarly to SLO1 K+ channels, cSrc blockers decreased significantly SLO3-mediated currents. Altogether these results are consistent with findings that hyperpolarization of the sperm plasma membrane is necessary and sufficient to prepare the sperm for the acrosome reaction and suggest that changes in sperm membrane potential are mediated by cSrc activation.